The Blockade of IL6 Counterparts the Osmolar Stress-Induced Apoptosis in Human Conjunctival Epithelial Cells - Hee-Jung Ju; Yong-Soo Byun; Jee-Won Mok; Choun-Ki Joo (Journal of Ophthalmology)
To determine the effect of hyperosmolarity on cell survival/apoptosis of conjunctival epithelial cells and evaluate the possible role of IL6, Wong-Kilbourne derivative of Chang conjunctival cell line (WKD) was used in this study. Confluent cells were incubated under different osmolarity (290 mOsm and 500 mOsm) with or without neutralizing IL6 antibody (50 ng/mL). The expression of IL6 level was measured in the supernatant of each conditioned medium. Cell viability/apoptosis assay was performed using Annexin V/Propidium Iodide (PI) and Cell Counting Kit-8 (CCK-8). Western blot was conducted to measure the abundance of apoptotic markers and IL6 related downstream signaling pathway. The concentration of IL6 showed time-dependent increase in cells treated with 500 mOsm. Although apoptosis of WKD cell is increased in treated 500 mOsm for 24 h, apoptosis reduced in WKD cell treated 500 mOsm with anti-IL6 for 24 h. Anti-IL6 inhibited the activation of JAK-STAT signaling pathway, which was induced by hyperosmolarity. Hyperosmolar condition induced apoptosis in conjunctival epithelial cells, along with increase of IL6 production. IL6 neutralizing antibody inhibited apoptosis and JAK-STAT signaling in hyperosmolar condition. These findings suggested that IL6 may be involved in apoptotic change and in hyperosmolarity.